2008
DOI: 10.1007/s10856-008-3395-4
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of tricalcium phosphate with Zn and Mg based dopants

Abstract: The purpose of this study is to prepare tricalcium phosphate (TCP) ceramic by dual dopants of magnesium (Mg) and zinc (Zn), and investigate the influence of dopants on the physical, mechanical and biological properties of TCP. TCP were synthesized with 1 wt% Mg, 0.3 wt% Zn and dual dopants using the precipitation process. Phase composition and microstructures were characterized. Mechanical properties and dissolution behavior in vitro were investigated. Human osteoblast cell culture was used to determine the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
140
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 158 publications
(146 citation statements)
references
References 27 publications
6
140
0
Order By: Relevance
“…In another study, a positive effect on the proliferation of the MC3T3 osteblastic cell line was observed in HA/TCP ceramics containing up to 1.3 wt.% zinc, whereas higher concentrations caused cytotoxicity [164]. A mildly positive effect of TCP ceramic doped with 0.3 wt.% zinc was also observed on the proliferation of human fetal bone tissue-derived osteoprecursor cell line [167]. The addition of zinc to brushite-forming b-TCP cement showed a positive effect on adhesion, proliferation, ALP activity and Col-I secretion of the MC3T3-E1 osteblastic cell line, an effect which was even more pronounced when both strontium and zinc were present in the cement [168].…”
Section: Zincmentioning
confidence: 89%
“…In another study, a positive effect on the proliferation of the MC3T3 osteblastic cell line was observed in HA/TCP ceramics containing up to 1.3 wt.% zinc, whereas higher concentrations caused cytotoxicity [164]. A mildly positive effect of TCP ceramic doped with 0.3 wt.% zinc was also observed on the proliferation of human fetal bone tissue-derived osteoprecursor cell line [167]. The addition of zinc to brushite-forming b-TCP cement showed a positive effect on adhesion, proliferation, ALP activity and Col-I secretion of the MC3T3-E1 osteblastic cell line, an effect which was even more pronounced when both strontium and zinc were present in the cement [168].…”
Section: Zincmentioning
confidence: 89%
“…[2,9] In our previous works, we have demonstrated that the mechanical and degradation properties of TCP can be tailored, without altering its inherent biocompatibility, by the addition of metal oxide dopants, such as NaF, TiO 2 , SiO 2 , CaO, ZnO and Ag 2 O. [10][11][12][13][14] Another interesting alternative to tailor the mechanical and biological properties of calcium phosphate based ceramics is to use biphasic calcium phosphate (BCP). BCPs composed of TCP and hydroxyapatite (HA) are gaining more importance because their biodegradation rate, bioactivity and osteoconductivity can be tailored by tuning the ratio of TCP to HA phases.…”
mentioning
confidence: 99%
“…Evis and Pinar Sun [34] demonstrate the β-TCP structure stabilization and the hydroxyapatite formation by the heat treatment above 800°C. Hot pressed magnesium fluoride has been used as a dome material for many devices due to its excellent mechanical strength and thermal stability [39][40][41]. The study conducted by Kim et al aimed to increase the mechanical properties and to inhibit the phase decomposition of HAp by the addition of MgF 2 in the HAp/ZrO 2 composites [37].…”
Section: +mentioning
confidence: 99%